Relationship between Pregnant Woman Obesity Grade-1 and Grade-2 with The Incidence of Preeklampsia - Mochammad Ilham, Ananda Frifiyant; Ariningtyas, Ninuk Dwi; Mochtar, Nur Mujaddidah; Marlina, Uning (MAGNA MEDICA Berkala Ilmiah Kedokteran dan Kesehatan, 2022)
Background: Preeclampsia is a hypertensive disorder that can increase maternal and fetal morbidity and mortality during pregnancy. Pregnant women with obesity are at higher risk of preeclampsia.Objective: To prove the relationship between pregnant women with grade-1 and grade-2 obesity and the incidence of preeclampsiaMethod: This study used the design of a prospective cohort. The population was pregnant women with obesity who got check-ups in Pregnancy Unit at Wiyung Sejahtera Hospital in Surabaya. This study used a consecutive sampling technique. The samples were pregnant women with BMI ≥ 25 with 34-38 weeks gestational age who signed the consent form. The data were analyzed through the Chi-Square test.Result: The results show that respondents who do not experience preeclampsia are dominated by pregnant women with grade-1 obesity by 70% and grade-2 obesity by 30%. Meanwhile, those who experience preeclampsia are dominated by pregnant women with grade-2 obesity by 75% and grade-1 obesity by only 25%. The results of the Chi-Square test analysis obtain a p-value of 0.007 with an odds ratio of 7,000.Conclusion: Pregnant women classified as grade-2 obesity have a seven times greater risk of experiencing preeclampsia compared to pregnant women with grade-1 obesity.